Nontraditional markets for Philippine exports - Tecson, Gwendolyn R. (1986)
The study analyzes the pattern of diversification of Philippine export flows over the last two decades as a clue to the problem of export expansion. Coefficients of concentration show a marked diversification in both geographic and commodity structures of Philippine export trade. In particular, there is found a 'healthy' shift away from traditional markets and towards nontraditional ones, including those of developing countries. Moreover, the commodity structure of the country's manufactured exports is seen to follow the general pattern of labor-intensity suggested by factor proportions theory, a pattern that is found to be reinforced over time. the findings are then interpreted in terms of their implications on policy making for export expansion, particularly of Philippine manufacture products.
Keywords: Exports -- Philippines; Foreign trade regulation